Calorimetry investigations of milled α-tricalcium phosphate (α-TCP) powders to determine the formation enthalpies of α-TCP and X-ray amorphous tricalcium phosphate. (1st September 2015) - Hurle, Katrin; Neubauer, Juergen; Bohner, Marc; Doebelin, Nicola; Goetz-Neunhoeffer, Friedlinde
Abstract : Graphical abstract: Abstract: One α- tricalcium phosphate ( α- TCP) powder was either calcined at 500 °C to obtain fully crystalline α- TCP or milled for different durations to obtain α- TCP powders containing various amounts of X-ray amorphous tricalcium phosphate (ATCP). These powders containing between 0 and 71 wt.% ATCP and up to 2.0 ± 0.1 wt.% β- TCP as minor phase were then hydrated in 0.1 M Na2 HPO4 aqueous solution and the resulting heat flows were measured by isothermal calorimetry. Additionally, the evolution of the phase composition during hydration was determined by in situ XRD combined with the G-factor method, an external standard method which facilitates the indirect quantification of amorphous phases. Maximum ATCP hydration was reached after about 1 h, while that of crystalline α- TCP hydration occurred between 4 and 11 h, depending on the ATCP content. An enthalpy of formation of −4065 ± 6 kJ/mol ( T = 23 °C) was calculated for ATCP (Ca3 (PO4 )2 ), while for crystalline α- TCP ( α- Ca3 (PO4 )2 ) a value of −4113 ± 6 kJ/mol ( T = 23 °C) was determined.